Dynamics of foraging and recruitment behavior in the Asian subterranean termite Coptotermes gestroi (Rhinotermitidae) - Arab, Alberto; Carollo Blanco, Yara [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Hindawi, 2012)
The present study investigated the trail-following behavior of the subterranean termite Coptotermes gestroi (Wasmann Rhinotermitidae) under laboratory conditions. The results showed that workers were the first to initiate the exploration to the food source. When food was discovered they returned to the nest laying a trail for recruiting nestmates to the food source. In this situation, workers always traveled significantly faster when returning from the arenas. Both workers and soldiers were recruited to the food source; however, the soldier/worker proportion was higher during the first phase of the recruitment. When no food was available, the number of recruited nestmates and the speed on their way back to the nest were significantly lower. The results also showed that scout foragers always laid trail pheromones when entering into unknown territories, and that chemical signals found in the food could induce workers of C. gestroi to increase their travel speed. Copyright © 2012 Alberto Arab et al.